2013
DOI: 10.5402/2013/921645
|View full text |Cite
|
Sign up to set email alerts
|

Tooth-Implant Connection: A Review

Abstract: Connecting teeth to osseointegrated implants presents a biomechanical challenge. is is due to the implant being rigidly �xed to the bone and the tooth being attached to the bone with a periodontal ligament. In order to overcome this problem, various connection types such as rigid and nonrigid have been proposed. However, the mechanism of attachment and the perceived problem of the differential support provided by the implant and the tooth have been discussed by many authors, and the ideal connection type is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…The use of both rigid and non-rigid connectors of different designs has been suggested to diminish these effects. 2,3 A study confirms that the stress-breaking action of the non-rigid connector, clarifying decrease of stresses within the implant by a factor of 24 when the force is applied on the tooth side. There are numerous reasons support the joining of teeth and implants.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The use of both rigid and non-rigid connectors of different designs has been suggested to diminish these effects. 2,3 A study confirms that the stress-breaking action of the non-rigid connector, clarifying decrease of stresses within the implant by a factor of 24 when the force is applied on the tooth side. There are numerous reasons support the joining of teeth and implants.…”
Section: Introductionmentioning
confidence: 65%
“…Finally, in periodontally compromised cases, the implants can provide stabilization of the teeth. 4,5 Tooth-to-implant connection can be a rational treatment choice in certain clinical situations, but that rigid connection should be used with caution particularly when there are periodontal problems. 6 It has been stated that the usage of tooth-implant supported prosthesis significantly reduce mechanical problems hazard once compared to implant supported prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Selection criteria is based on the number and condition of the remaining teeth, space available, adequacy of bone support, patient's desire and economic factors. If planning for implant treatment, implant only supported fixed prosthesis remains the treatment of choice but certain situations necessitate the use of tooth implant supported prosthesis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews to assess the survival and complication rates of fixed partial dentures (FPDs) indicated that the survival rates for both implants and reconstructions combined with tooth implant-supported prosthesis (TISP) were lower than those reported for implant-only supported prosthesis [ 1 5 ]. Historically, connecting a tooth to an implant is discouraged because differences in tooth and implant mobility would result in the prosthesis being cantilevered to stress the implant [ 2 5 ]. However, splinting the implant and natural tooth is occasionally used as a rational alternative for anatomical structural reasons or patient-centered preferences [ 1 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, connecting a tooth to an implant is discouraged because differences in tooth and implant mobility would result in the prosthesis being cantilevered to stress the implant [ 2 5 ]. However, splinting the implant and natural tooth is occasionally used as a rational alternative for anatomical structural reasons or patient-centered preferences [ 1 5 ]. Endodontically treated tooth restored used a post and core build-up and full crown is occasionally regarded as an abutment tooth in a TISP with healthy periodontal stability and in dense bone situations [ 4 , 6 – 12 ].…”
Section: Introductionmentioning
confidence: 99%